Stochastic stability and stationary probability density analysis for a nutrient–phytoplankton model with multiplicative and additive noises. (October 2022) - Ma, Yuanlin; Yu, Xingwang
Abstract: In this paper, the stability and stationary probability density for a stochastic nutrient–phytoplankton model with multiplicative and additive noises are explored. We first transform the original system into an Itô diffusion system by using Khasminskii transformation and stochastic averaging method. After that, we employ singular boundary theory to analyze the stability of the system. We then derive the stationary probability density of the averaging amplitude equation by the corresponding Fokker–Planck–Kolmogorov equation. Finally, the theoretical results are verified by numerical simulations and the influence of noise on system dynamics is further illustrated.